Optimal Design of Mixed Structures under Time-history Loading Using Metaheuristic Algorithm - Kaveh, Ali; Ardebili, Shaylin Rezazadeh (Periodica Polytechnica Civil Engineering, 2023)
In this paper, an optimum design of concrete-steel mixed frames under time-history loadings was formulated as an optimization problem. The behavior of a mixed structure is different from the steel and reinforced concrete structures because of vertically irregular in their mass, stiffness and damping of each part. Moreover, current codes and available commercial software packages do not present solutions for such structures. Researches have indicated that the structures exhibit higher-mode effects and responses that are sensitive to the relative stiffness and mass of the two parts of the structures. Thus, the equivalent static analysis is not applicable, a dynamic analysis has to be performed to analyze and design such structures. Therefore, the optimum design of mixed structures under an earthquake can be relatively complicated and time-consuming. Because the design methods for these structures are iterative and dynamic. The main objective is to find the minimum cost of the structure under time-history loadings while satisfying all design constraints. The results show that the proposed optimization procedure is ideal to obtain the optimum design for a mixed structure subjected to time-history loadings. Also, for comparison, the optimal design of reinforced concrete (RC) frames and steel frame are presented using the algorithm.